RECENT DRUG DISCOVERY STATUS AGAINST PEPTIC ULCER - Panda, Girija Shankar; Sahoo, Deeptitapa; Ray, Jassaswi; Mohanty, R.; Nayak, Ritesh Kumar (Journal of Global Pharma Technology, 2024)
Peptic ulcer is a customary disease, it affecting around 5-10% of the general population worldwide, but with notable regional and rectal variants. The two most common etiological causes are the chronic infection with Helicobacter Pylori (HP) and the uses of nonsteroidal anti-inflammatory drugs (NSAIDS). Its diagnosis is based mainly in the endoscopy and the active search of contaminant Helicobacter pylori presence. Peptic ulcers are found to be due to an imbalance between aggressive factors such as hydrochloric acid, pepsin, refluxed bile, leukotrienes, relative oxygen species and defensive factors, which include the function of the mucus, bicarbonate barrier, prostaglandins, mucosal blood flow, cell renewal and migration, non-enzymatic and enzymatic antioxidants and some growth factors. Keywords: Helicobacter Pylori, NSAID, Proton Pump Inhibiter, Leukotriene, Bicarbonate Barrier, Refluxed Bile.